Duplex Stainless Steel Castings
By reasonably adding elements such as Cr, Si, Ni, etc. to the castings where biomass air is blown into the nozzle, and controlling the distribution of austenite in the ferrite matrix, the problem of insufficient wear resistance and corrosion resistance of the nozzle in a high-temperature composite atmosphere is solved, and its service life is significantly extended.
Patent Information
- Application Number
- JP2021013103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-01-29
AI Technical Summary
When used in high-temperature environments, the existing biomass air blowing nozzles are prone to short life due to sand wear, chloride corrosion, sulfur oxidation corrosion and oxidation corrosion, and the prior art is difficult to effectively improve its corrosion resistance in a composite atmosphere.
Two-alloy steel castings with reasonable addition of Cr, Si, Ni and other elements are used to improve the corrosion resistance of the nozzle by controlling the element content and the distribution of austenite in the ferrite matrix.
It significantly improves the wear resistance and corrosion resistance of the biomass air blowing nozzle in a high-temperature composite atmosphere, and extends its service life.
Smart Images

Figure 0007658555000001 
Figure 0007658555000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a duplex stainless steel casting, and more particularly to a duplex stainless steel casting having excellent high-temperature corrosion resistance. [Background technology]
[0002] In recent years, the use of biomass resources has been considered as an attempt to reduce the use of fossil fuels. Biomass resources are attracting attention because they are a way to reuse resources that would otherwise be discarded, and their use for combustion can lead to a reduction in the use of fossil fuels.
[0003] Biomass boilers are a type of boiler that is widely used, in which a furnace is filled with inert inorganic material such as sand as a bed material that acts as a heat carrier, and combustion gas is blown in from the hearth through an air blowing nozzle to agitate the bed material, allowing the material to be treated to be combusted while maintaining the bed material at a desired temperature.
[0004] In recent years, as various biomass resources are used as fuel, problems have arisen such as oxidation by H2O, CO2, and O2, chlorination by chlorine generated from plastic fuels, and corrosion by sulfur dioxide generated from waste tires. Corrosion is a phenomenon in which corroded Cl, S, and O form a corrosion layer on the matrix of the air blowing nozzle, which then evaporates or peels off.
[0005] Patent Document 1 discloses a high alloy steel for waste heat boiler tubes in waste incinerators that generate molten salt and has excellent resistance to stress corrosion cracking and intergranular corrosion.
[0006] Patent Document 2 discloses a high-temperature corrosion-resistant steel having excellent hot workability.
[0007] Patent Document 3 discloses a highly corrosion-resistant austenitic stainless steel for use in heat transfer tubes in boilers at waste disposal plants, and proposes an austenitic stainless steel for use in boiler heat transfer tubes that has excellent resistance to intergranular corrosion, molten salt corrosion, and acid dew-point corrosion.
[0008] Patent Document 4 discloses a nozzle material that is highly resistant to wear caused by sand. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 4-350149 [Patent Document 2] Japanese Patent Application Publication No. 7-268565 [Patent Document 3] JP 2000-192201 A [Patent Document 4] JP 2017-78198 A Summary of the Invention [Problem to be solved by the invention]
[0010] Air blowing nozzles for biomass are used in high-temperature environments, so when manufacturing the nozzles from castings, it is important to take measures against abrasion caused by sand and other fluidized bed media, as well as corrosion caused by chlorination, sulfidation, and oxidation.
[0011] The air blowing nozzles used in the hearth of a biomass boiler are made of heat-resistant cast steel (JIS G 5122 SCH22) or stainless steel cast steel (JIS G 5121 SCS13A), but their service life is extremely short due to wear from sand and corrosion from chlorination, sulfidation, and oxidation.
[0012] Patent Documents 1 to 3 concern plastically processed products, which are subjected to plastic processing such as hot forging. In contrast, the air blowing nozzle is a cast product that is not subjected to plastic processing after being cast into a predetermined shape. The alloy structure of the casting is different from the alloy structure produced by plastic processing, and is the solidified structure at the time of casting that remains as it is. Since castings can be obtained in any shape by pouring molten metal into a mold, they have the advantage of being easier to manufacture than plastically processed products. On the other hand, the solidified structure of the casting has large segregation and coarse crystal grains, which is said to affect corrosion resistance.
[0013] Patent Document 4 discloses cast iron that can be used for nozzles and has excellent resistance to wear caused by sand, but there is room for improvement in terms of corrosion resistance in a composite gas atmosphere.
[0014] In view of the above circumstances, an object of the present invention is to provide a casting that has excellent abrasion resistance and corrosion resistance in a high-temperature complex gas atmosphere and can be used for an air blowing nozzle for biomass. [Means for solving the problem]
[0015] The present inventors have conducted extensive research into the component composition of a steel casting having excellent corrosion resistance in a complex gas atmosphere at high temperatures.
[0016] In an oxidizing atmosphere such as H2O or O2, Cr forms stable Cr2O3 or FeCr2O4, which is effective in improving high-temperature corrosion resistance. However, in a combustion gas atmosphere containing SO2 or Cl2, CrS or CrCl2 is formed. As the sulfurization reaction progresses, the amount of Cr in the matrix decreases, lowering corrosion resistance. Similarly, as the chlorination reaction progresses, the reaction product evaporates, reducing the amount of Cr in the matrix and lowering corrosion resistance. It is known that the addition of Si is effective in suppressing the decrease in corrosion resistance caused by the decrease in the amount of Cr in the matrix.
[0017] The present inventors further found that by adding an appropriate amount of Ni, an appropriate amount of austenite is dispersed in the ferrite matrix, improving the adhesion of the corrosion coating. Furthermore, the dispersion of austenite suppresses the coarsening of the ferrite structure, resulting in fine crystal grains. As a result, the duplex stainless steel castings to which an appropriate amount of Ni is added have remarkable corrosion resistance in a mixed gas atmosphere of chlorine, sulfur, and oxygen at high temperatures.
[0018] The present invention has been made based on the above findings, and the gist of the present invention is as follows.
[0019] (1) A duplex stainless steel casting characterized by containing, by mass%, one or more of C: 0.08% or less, Si: 2.50 to 4.00%, Mn: 0.30 to 2.00%, Cr: 18.00 to 22.00%, Ni: 2.00 to 10.00%, Se: 0 to 0.50%, Te: 0 to 0.100%, Bi: 0 to 0.50%, Mo: 0 to 8.00%, B: 0 to 0.030%, Ce: 0 to 0.20%, La: 0 to 0.20%, and Mg: 0 to 0.20%, and one or more of W: 0 to 2.00%, Nb: 0 to 2.00%, Ti: 0 to 2.00%, and Al: 0 to 5.00%, with the balance being Fe and impurities.
[0020] (2) The duplex stainless steel casting according to (1) above, characterized in that the ferrite matrix contains austenite at an area ratio of 5 to 40%.
[0021] (3) The duplex stainless steel casting according to (1) or (2) above, characterized in containing, by mass%, one or more of Se: 0.001% to 0.50%, Te: 0.001% to 0.100%, and Bi: 0.001% to 0.50%.
[0022] (4) The duplex stainless steel casting according to any one of (1) to (3) above, characterized in that it contains, by mass%, 1.00 to 8.00% Mo.
[0023] (5) The duplex stainless steel casting according to any one of (1) to (4) above, characterized in that it contains, by mass%, 0.001 to 0.030% B.
[0024] (6) The duplex stainless steel casting according to any one of (1) to (5) above, characterized in containing, by mass%, one or more of Ce: 0.001 to 0.20%, La: 0.001 to 0.20%, and Mg: 0.001 to 0.20%.
[0025] (7) The duplex stainless steel casting according to any one of (1) to (6) above, characterized in containing, by mass%, one or more of W: 0.001 to 2.00%, Nb: 0.001 to 2.00%, Ti: 0.001 to 2.00%, and Al: 0.001 to 5.00%.
[0026] (8) An air blowing nozzle made of the duplex stainless steel casting according to any one of (1) to (7). Effect of the Invention
[0027] According to the present invention, it is possible to provide a casting for an air blowing nozzle for biomass that has corrosion resistance in a complex gas atmosphere in a high temperature range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will be described in detail below. First, the composition of the heat-resistant, wear-resistant cast iron of the present invention will be described. Hereinafter, "%" in the composition of the components means "% by mass".
[0029] C combines with Cr in the steel and precipitates as Cr carbides at the grain boundaries. When Cr precipitates as carbides, the Cr concentration in the matrix decreases and high-temperature oxidation resistance deteriorates, so it is preferable to have a low C content. Therefore, the C content is set to 0.08% or less, preferably 0.05% or less.
[0030] Silicon acts as a deoxidizer and is necessary to improve oxidation resistance and corrosion resistance, especially at high temperatures. To fully obtain this effect, the silicon content is set to 2.50% or more. In consideration of sigma embrittlement, the silicon content is set to 4.00% or less, preferably 3.50% or less.
[0031] Mn is an austenite forming element and is also a useful component as a deoxidizer and desulfurizer. To fully obtain these effects, the Mn content is set to 0.30% or more. From the viewpoint of preventing embrittlement of cast iron and deterioration of creep strength, the upper limit of the Mn content is set to 2.00% or less.
[0032] Cr is an element that improves high-temperature strength and oxidation resistance at high temperatures. To fully obtain this effect, the Cr content is set to 18.00%. In an environment where molten chlorides adhere, such as a biomass boiler, if the Cr content is too high, volatile Cr2O2Cl2 is formed and high-temperature oxidation resistance decreases, so the Cr content is set to 22.00% or less.
[0033] Ni is an austenite forming element and improves high temperature strength and corrosion resistance at high temperatures. It also has the effect of increasing the amount of work hardening and enhancing wear resistance. In the present invention, by including 2.00 to 10.00% of Ni, austenite in the ferrite matrix is dispersed and the adhesion of the corrosion coating is improved. Furthermore, this inhibits the coarsening of the ferrite structure, refines the crystal grains, and improves corrosion resistance in a composite gas atmosphere of chlorine, sulfur, and oxygen in the high temperature range.
[0034] The preferred amount of austenite dispersed in the ferrite matrix is 5 to 40% in terms of area ratio. The area ratio of austenite can be determined from a two-tone image obtained by observing the metal structure with an optical microscope.
[0035] Generally, duplex stainless steel is difficult to cut, and therefore has the problem of high cutting costs. In order to improve machinability, the duplex stainless steel casting of the present invention can further contain one or more of Se, Te, and Bi. The addition of these elements is not essential. Although even a small amount of these elements can improve machinability, in order to fully obtain the effect of the addition, it is preferable to add 0.001% or more of any element. If the content of these elements is too high, the effect will simply saturate, so the upper limit of the content is 0.50% for Se, 0.100% for Te, and 0.50% for Bi.
[0036] The addition of Se, Te and Bi has the effects of reducing cutting resistance, extending tool life, suppressing built-up edge, improving the finished surface properties and improving chip crushability.
[0037] However, the addition of these elements reduces hot workability, making them undesirable for forging or rolling. Since the duplex stainless steel castings of the present invention are as-cast castings, the reduction in hot workability is not a major problem, and the addition of Se, Te and Bi is effective in improving machinability.
[0038] The duplex stainless steel casting of the present invention may further contain Mo. The addition of Mo is not essential. Mo dissolves in austenite and has the effect of increasing wear resistance. This effect can be obtained even with a small amount of Mo added, but in order to fully obtain the effect of the addition, it is preferable that the Mo content is 1.00% or more. Even if the Mo content is high, the effect is saturated and there is a possibility of a decrease in toughness due to segregation, so the upper limit is set to 8.00%.
[0039] The austenitic stainless steel castings of the present invention can further contain B. The addition of B is not essential. B improves hot workability and prevents casting cracks by segregating to grain boundaries as solid solution B. This effect can be obtained even with a small amount of B added, but to fully obtain the effect of the addition, it is preferable to make the B content 0.001% or more. Even if the B content is high, the effect saturates and there is a possibility of a decrease in toughness due to segregation, so the upper limit is set to 0.030%.
[0040] The duplex stainless steel casting of the present invention may further contain one or more of Ce, La, and Mg. The addition of these elements is not essential. These elements combine with S to suppress the grain boundary segregation of S and suppress the decrease in toughness. Even a small amount of these elements has the effect of suppressing the precipitation of Cr sulfides, but in order to fully obtain the effect of the addition, it is preferable to add 0.001% or more of any element. For each element, the effect saturates when the content exceeds 0.20%, so the upper limit is set to 0.20%.
[0041] The duplex stainless steel casting of the present invention may further contain one or more of W, Nb, Ti, and Al. The addition of these elements is not essential. These elements are easy to form carbides, so they can fix C in the steel and suppress the precipitation of Cr carbides, thereby preventing a decrease in high-temperature strength. Even a small amount of these elements has the effect of suppressing the precipitation of Cr carbides, but in order to fully obtain the effect of the addition, it is preferable to add 0.001% or more of any element. Since the effect of each element saturates when the content is high, the upper limit of W, Nb, and Ti is 2.00%, and the upper limit of Al is 5.00%.
[0042] The balance of the composition is Fe and inevitable impurities. The inevitable impurities refer to those that are inevitably mixed in from the raw materials or the manufacturing environment when a casting having the composition specified in the present invention is industrially manufactured, and examples of such impurities include P and S. P and S are usually mixed in the casting at about 0.030% or less.
[0043] The manufacturing method of the present invention is not particularly limited, and may be a conventional method. First, a molten metal having the above-mentioned component composition is prepared, the molten metal is poured into a mold, and the poured molten metal is cooled and solidified. In principle, the cast iron of the present invention is used as it is cast, but it can be subjected to a solution treatment as necessary.
[0044] By casting a molten metal having the component composition of the present invention, it is possible to obtain a duplex stainless steel casting having excellent high-temperature corrosion resistance in the as-cast state without using any special manufacturing method.
[0045] The duplex stainless steel casting of the present invention is a steel that is not subjected to plastic processing after being cast into a mold of a predetermined shape, and is distinguished from alloys that have been subjected to plastic processing such as hot rolling or forging. That is, the casting has a solidification structure as cast as an alloy structure, whereas the alloy that has been subjected to plastic processing has an alloy structure generated by processing, and the structures are significantly different. In the casting of the present invention, the crystal grain size is about 0.2 to 10.0 mm. EXAMPLES
[0046] The present invention will be described in more detail below with reference to examples. The examples given below are merely examples of the embodiments of the present invention, and it goes without saying that the present invention is not limited to the following examples.
[0047] [Example 1] A cylindrical air blowing nozzle with an outer diameter of 70 mm and an inner diameter of 56 mm and the component composition shown in Table 1 was installed in a biomass boiler with an atmosphere of chlorine, sulfur, and oxygen, and an actual experiment was conducted. One year after installation, the outer diameter of the nozzle was measured with a vernier caliper, and the wear resistance and corrosion resistance of the nozzle were evaluated based on the amount of diameter reduction. Table 1 shows the amount of diameter reduction measured for nozzles with each component composition.
[0048] Nos. 1 to 15 in Table 1 are inventive examples using the steel of the present invention, and Nos. 21 to 23 are comparative examples using general steel. As shown in Table 1, it was confirmed that the nozzles using the castings of the present invention were less abraded and corroded even when used in biomass boilers, and had excellent abrasion resistance and corrosion resistance in high temperature ranges.
[0049] [Table 1]
[0050] [Example 2] For the castings having the component compositions No. 1, 11, 12, and 13 shown in Table 1, a drill (SKH51, drill diameter 5.0 mm) was used to repeatedly drill holes to a depth of 20 mm without cutting oil, at a cutting speed of 20 m / min and a feed rate per revolution of 0.1 mm / rev, and the number of holes until drilling became impossible was determined to evaluate the machining performance. The results are shown in Table 2. The machining efficiency is the ratio of the number of times that drilling is possible to the number of times that drilling becomes impossible with casting No. 1 taken as 1.
[0051] It was confirmed that Nos. 11, 12, and 13, which had machinability-improving elements added, had high corrosion resistance as shown in Example 1, and at the same time showed higher machining performance than No. 1. Nos. 24 and 25 are forged steels whose composition is within the range of the composition of the castings of the present invention. Steel No. 24 showed machining performance equivalent to that of the castings of the present invention. However, No. 25, which had machinability-improving elements added like No. 7, had reduced hot workability, so it developed forging cracks and the desired steel could not be obtained. [Table 2]
Claims
1. In mass percent, C: 0.08% or less, Si: 2.50-4.00%, Mn: 0.30-2.00%, Cr: 18.00-22.00%, Ni: 2.00-10.00%, Se: 0-0.50%, Te: 0 to 0.100%, Bi: 0 to 0.50%, Mo: 0-8.00%, B: 0.001-0.030%, One or more of Ce: 0 to 0.20%, La: 0 to 0.20%, and Mg: 0 to 0.20%, and One or more of W: 0-2.00%, Nb: 0-2.00%, Ti: 0-2.00%, and Al: 0-5.00%. The balance is Fe and impurities.
1. A duplex stainless steel casting comprising:
2. 2. The duplex stainless steel casting according to claim 1, characterized in that the ferrite matrix contains austenite at an area ratio of 5 to 40%.
3. The duplex stainless steel casting according to claim 1 or 2, characterized in that it contains, in mass%, one or more of Se: 0.001 to 0.50%, Te: 0.001 to 0.100%, and Bi: 0.001 to 0.50%.
4. The duplex stainless steel casting according to any one of claims 1 to 3, characterized in that it contains, in mass%, Mo: 1.00 to 8.00%.
5. The duplex stainless steel casting according to any one of claims 1 to 4, characterized in that it contains, in mass%, one or more of Ce: 0.001 to 0.20%, La: 0.001 to 0.20%, and Mg: 0.001 to 0.20%.
6. The duplex stainless steel casting according to any one of claims 1 to 5, characterized in that it contains, in mass%, one or more of W: 0.001 to 2.00%, Nb: 0.001 to 2.00%, Ti: 0.001 to 2.00%, and Al: 0.001 to 5.00%.
7. An air blowing nozzle made of the duplex stainless steel casting according to any one of claims 1 to 6.
Citation Information
Patent Citations
Stainless cast steel
JP1978113215A
Fe-cr-ni-al-si alloy having resistance to sulfurization corrosion
JP1986113748A
Free-cutting duplex stainless steel casting
JP1990163347A
Two-phase stainless steel for building material
JP1990305940A
High alloy steel for trash incineration waste heat boiler tube
JP1992350149A